Agronomic and economic feasibility of tomato and lettuce intercropping in a soilless system as a function of the electrical conductivity of the nutrient solution - Da Cunha-Chiamolera, Tatiana Pagan Loeiro [UNESP]; Urrestarazu, Miguel; Filho, Arthur Bernardes Cecílio [UNESP]; Morales, Isidro (American Society for Horticultural Science, 2017)
An intercrop is studied here as a new way of farming in soilless systems within a protected environment. To estimate the efficiency of intercropping in this cultivation system, an experiment was conducted to evaluate the effect of the electrical conductivity (EC) of the nutrient solution (2.0, 2.5, and 3.0 dS·m−1) on lettuce and tomato plants and on the agronomic and economic feasibility of the intercrop compared with monoculture. The results indicated that a moderate increase in EC from 2.0 to 3.0 dS·m−1 did not exert any important effect on tomato plant production or quality but did cause a decrease in lettuce yield in both the first and second crops. Intercropping was only feasible for lettuce when the tomato and lettuce plants were transplanted on the same day. The highest tomato (G class) and lettuce yields were achieved at an EC of 2.5 dS·m−1; this condition resulted in the highest intercrop profitability (0.53 €·m−2 more) when compared with tomato monoculture.
Keywords: Greenhouse; Lactuca sativa; Soilless culture; Solanum lycopersicum